Factors associated with training needs among agriculture extension officers in central Iraq - Saleh, Jasim Mohammed (2017)
The analysis of training needs is not a task for specialists alone. Managers today are often responsible for many forms of employees management, including the training and development of their team, and should therefore have an understanding of training needs analysis and be able to implement it successfully. There are poor skills, dismal performance, working conditions, business, job skills, communication skills and lack of courses are among the issues that confront administrators in the agriculture sector. If they currently did not have access to a microcomputer and their budgetary restraints would not allow them to purchase one in the near future, their opportunity to use inservice would be low, whereas agriculture is more dynamic nowadays. Due to the flux state of ICT, the need for training becomes necessary. The study in hand addressed training requirements for extension agents in Iraq. The objectives of this study were: 1) To describe the socio-demographic characteristics of the respondents; 2) To identify the level of training needs of the respondents in the areas of agricultural extension; 3) To compare the relationship among training course, scientific specialization, and socio-demographic factors; 4) To determine the relationship between training needs of the respondents in agricultural extension work areas and socio-demographic factors, and 5) To explore the existence of significant differences in the training needs of the respondents according to the variables. This study had been conducted in three (3) selected Iraqi provinces, namely Baghdad, Wasit, and Babylon. For data collection, 300 agricultural extension officers were interviewed using survey questionnaire stratified sampling. Borich Needs Assessment Model was used in determining the structure of the training needs. The statistical analysis techniques used in the study include descriptive analysis, T-Test, Chi-Square, one-way analysis of variance ANOVA and correlation analysis. More than one-third (36.95%) of the respondents aged between 31 to 40 years old, the majority were male (63.77%) and married (73.19%). For academic qualification, (71.74%) of the respondents possess a baccalaureate degree, (40.94%) have been working between 1-5 years and the majority of the respondents had attended training (81.16%). The study shows that the highest benefit of training courses attended is the crop planting course. For the training needs, the highest training need was the extension methods (M = 3.74), while the middle skills is the use of computer and ICT (M = 3.26) and the least skills is management (M = 3.15), indicating that they are a strongly needed training in these areas. Furthermore, the results show that there is a significant relationship between training needs and the province, marital status, location of work, training, number of training courses attended (r = 0.14), job satisfaction (r = 0.33), information (r = 0.43), age and the organizational characteristics (r = 0.52). In addition, the findings also show that there is a non-significant relationship with gender, education level, background of family, origin, specialization, and experiences in agricultural extension and farming. This study indicates that there was a need for training in multiple areas of the agricultural sector. In order to have a training program that meets all the aspirations to promote the agricultural sector, more studies in training are needed so that employees can demonstrate a high level of competency and it also can help them to be accustomed to different surroundings and environments. Should be focus on staff organizational characteristics, job satisfaction, information and follow the weakness in any area and create a subjective rating of these skills by specialists. Based on the findings of the study, it is recommended that good quality training programs be launched that could target the weaknesses, make improvements, enhance the competence and upgrade the skills of extension workers. This will enable extension professionals to be more confident, knowledgeable, and sufficiently productive to serve the diverse needs of the farmers while realizing sustainable agriculture.